Hubungan Antara Kecanduan Smartphone Dengan Psychological Well-being Pada Remaja - Jumrianti, Feni; Nugroho, Sigit; Arief, Yanwar (UIR Press, 2022)
Smartphone addiction is a habit or behavior that cannot be controlled when hold or use a smartphone. That behavior changes the human personality that interfere with their daily habits and activities. The purpose of this study was to determine the relationship between smartphone addiction and psychological well-being in adolescents. This study uses Quantitative Method with 349 adolescents, aged 10-22 years old (according to the Regulation of the Minister of Health of the Republic of Indonesia number 25 of 2014 and John Santrock 2003) with smartphones usage habit. By using Non Probability sampling technique, namely Convenience Sampling, using the SAS-SV (Smartphone Addiction Scale Short Version) scale and the Ryff Psychological well-being scale has distributed via google form. The results of this study obtaine a correlation coefficient value (r) = -0.255 and a significance value of 0.000 (ρ<0.05). This result shows the relationship between smartphone addiction and psychological well-being in adolescents.